Results : think less, achieve more - Smart, Jamie, (Business consultant) (Hoboken : Capstone, 2017)
"Life can be a bit overwhelming sometimes, right? It can be difficult to clear your mind of a million different anxieties and focus in on the one thing you need to get done. Bestselling author of Clarity and The Little Book of Clarity goes one step further with Results by using his Clarity Coaching Model to help you de-clog your mind so you can make better decisions, prioritise and focus on achieving those important goals. Develop a deeper understanding of why you act the way you do and awaken your inner potential. Jamie's transformational coaching techniques will help you improve in all areas of your life, from developing your listening skills during meetings at work to reducing the levels of stress in your life. These techniques will see you through three important changes - your personal transformation that will see you gaining confidence and understanding your own behaviour, your interpersonal transformation to guide you in having an impact on those around you, and lastly your commercial transformation to get your professional life moving in the direction you want. Results is full of helpful examples and exercises to get you on the road to the results you need. Learn how to: Prioritise and focus on the right goals at the right time Achieve the results you want by following the Clarity Coaching Model Improve your overall performance to gain better relationships with your colleagues, close friends and family Add more purpose to your life by allowing time for creativity and innovation Encourage others to follow in your footsteps!"--
"The book will use many of the examples, exercises and metaphors that have been tried and tested for many years, and that form the heart of the Certified Clarity Coach Training Programme"--
Machine generated contents note: Preface Foreword Introduction Part One: Grounding - Your Personal Transformation 1 You're Built For Reality: You're Optimised For Results 2 The One and Only Way Your Mind Always Works 3 Eliminating worry, anxiety and fear of criticism 4 The Source of Resourcefulness, Resilience and Results 5 Finding Your Place of Meaning, Passion and Purpose 6 Leadership: The Inner Key to Confidence and Certainty 7 The Liberating Truth About Goals 8 Moving from Resistance to Action Part Two: Impact - Your Interpersonal Transformation 9 The principles of impact 10 The secret of powerful connection 11 The source of superb performance 12 The Catalyst for Transformational Results 13 The only two challenges that stop people making progress 14 Finding your bearings when you get knocked off-track 15 Making Good Decisions: Wisdom, Intuition and Common Sense 16 The source of impact, innovation and disruption Part Three: Leverage - Your Commercial Transformation 17 Ignite your entrepreneurial instincts 18 Tribal marketing: Engaging with Your Audience 19 The only things anyone ever pays for 20 Influence, motivation and zero-pressure selling 21 Turning your ideas into reality 22 Leveraging results exponentially 23 The key to creating transformational experiences 24 Prospering in the transformation economy Acknowledgements Further Explorations Clarity Clarity Consulting World Clarity Foundation About Jamie Smart Index.
Includes index.
Keywords: Insight; Thought and thinking; Decision making